2017
DOI: 10.1002/ps.4511
|View full text |Cite
|
Sign up to set email alerts
|

The adverse impact of the neonicotinoid seed treatment ban on crop protection in oilseed rape in the United Kingdom

Abstract: This paper describes the consequences of the ban on neonicotinoid seed treatments on pest management in oilseed rape. Since the ban was implemented in December 2013, there have been serious crop losses in 2014, 2015 and 2016 owing to cabbage stem flea beetles, Psylliodes chrysocephala, and aphids, Myzus persicae, which have developed resistance to the alternative pyrethroid sprays that were employed to control them. This has resulted in increased crop losses, decreased yields and a substantial decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 5 publications
1
39
0
Order By: Relevance
“…The increase in the average weight of plants in the thiamethoxam variant was observed as a result of the prevention of CSFB injury. A very low susceptibility of CSFB to thiacloprid and also to acetamiprid was reported by Dewar [29].…”
Section: Discussionmentioning
confidence: 92%
“…The increase in the average weight of plants in the thiamethoxam variant was observed as a result of the prevention of CSFB injury. A very low susceptibility of CSFB to thiacloprid and also to acetamiprid was reported by Dewar [29].…”
Section: Discussionmentioning
confidence: 92%
“…With the exception of the limited case-study-based findings following the EU neonicotinoid ban (Kathage et al 2018;Scott and Bilsborrow 2019;Dewar 2017), there are no large scale empirical studies that document and estimate the impacts of widespread neonicotinoid use. In addition, there is no existing work that uses farm-level data to estimate and disentangle the impacts of both NeoST and GE trait adoption on the likelihood of using specific insecticide groups, nor do any previous studies estimate their impacts on toxicity risk for different species.…”
Section: These Insecticide Regression Models Are Informative About Thmentioning
confidence: 99%
“…Organophosphates are widely considered more dangerous for applicators and mammals than neonicotinoids (Hurley and Mitchell 2017), and pyrethroids are highly toxic to aquatic life and often as toxic to non-target insects (Douglas and Tooker 2016). Empirical evidence of substitution into these insecticides has recently been documented in the EU, where it has been found that the EU neonicotinoid ban has led to increases in the use of alternative soil and foliar applied insecticides in 3 both maize (Kathage et al 2018) and oilseed rape production (Kathage et al 2018;Scott and Bilsborrow 2019;Dewar 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Being susceptible to numerous pests, OSR crops 41 were, until the European Union moratorium in 2013, treated with neonicotinoids (Gross 2013; Dewar, 42 2017). Since this ban, there have been crop losses and reductions in yields in eastern England from 43 cabbage stem flea beetles (Dewar 2017); in some instances emergency use of neonicotinoids on OSR 44 crops has been granted (Case 2015). With a decision yet to be made on whether the European Union 45 moratorium will continue and with the UK voting to leave the European Union (and hence having to 46 determine its own policy on neonicotinoid pesticides), evidence is needed on how much honeybees 47 and wild bees utilise OSR crops (Woodcock et al 2016).…”
Section: Introduction 24mentioning
confidence: 99%